2001
DOI: 10.1046/j.1570-7458.2001.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

A differential interaction study of Bemisia tabaci Q‐biotype on commercial tomato varieties with or without the Mi resistance gene, and comparative host responses with the B‐biotype

Abstract: Three tomato varieties (Motelle, Ronita, and VFN8) bearing the Mi-1.2 gene providing resistance to nematodes Meloidogyne spp. and to the potato aphid Macrosiphum euphorbiae Thomas, and three varieties not bearing this gene (Moneymaker, Roma, and Río Fuego), were compared by choice assay for host preference using the Qbiotype of Bemisia tabaci (Gennadius). The most preferred hosts, determined by infestation levels and numbers of feeding adults were Moneymaker, Río Fuego and Roma, all of which were not carrying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 20 publications
2
41
0
2
Order By: Relevance
“…Host Method of observation Dharne and Kabre, (2009) Chili TMB (leaf turn method) Zabel et al (2001) Tomato NDM Gencsoylu (2009) Cotton TMB (leaf turn method) Ali et al (2004) Brinjal TMB (leaf turn method) Manzano et al (2003) Snap bean Cotyledonary leaf (leaf turn method) Akhtar et al (2004) Cotton TMB (leaf turn method) Sanchez-Pena et al (2006) Brinjal NDM Gupta and Pathak (2009) Black Gram NDM Byrne (2010) Poinsettia Leaf turn method Pasian et al (2000) Chrysanthemum and Gerbera Entire plant counting Castle et al (2009) Melon vine Fifth terminal leaf (leaf turn method) Lee et al (2002) Tomato NDM Sequeira and Naranjo (2008) Cotton Abaxial side of single leaf (leaf turn method) Alicai (1999) Sweet potato NDM Leite et al (2003) Brinjal TMB (leaf turn method) Nombela et al (2001) Tomato Counting on all leaves of each plant Mallah et al (2001) Cotton TMB (leaf turn method) Muniz et al (2002) Tomato and Pepper TMB (leaf turn method) Muqit et al (2008) Tomato NDM Rafiq et al (2008) Araceae, Asteraceae, Brassicaceae, Cucurbitaceae, Chinopodiaceae, Malvaceae, Meliaceae, Papilionaceae and Solanaceae NDM Leite et al (2005) Okra TMB (leaf turn method) Naranjo et al (2003) Cotton NDM *TMB-Top, middle and bottom, **NDM-No defined method.…”
Section: Referencementioning
confidence: 99%
“…Host Method of observation Dharne and Kabre, (2009) Chili TMB (leaf turn method) Zabel et al (2001) Tomato NDM Gencsoylu (2009) Cotton TMB (leaf turn method) Ali et al (2004) Brinjal TMB (leaf turn method) Manzano et al (2003) Snap bean Cotyledonary leaf (leaf turn method) Akhtar et al (2004) Cotton TMB (leaf turn method) Sanchez-Pena et al (2006) Brinjal NDM Gupta and Pathak (2009) Black Gram NDM Byrne (2010) Poinsettia Leaf turn method Pasian et al (2000) Chrysanthemum and Gerbera Entire plant counting Castle et al (2009) Melon vine Fifth terminal leaf (leaf turn method) Lee et al (2002) Tomato NDM Sequeira and Naranjo (2008) Cotton Abaxial side of single leaf (leaf turn method) Alicai (1999) Sweet potato NDM Leite et al (2003) Brinjal TMB (leaf turn method) Nombela et al (2001) Tomato Counting on all leaves of each plant Mallah et al (2001) Cotton TMB (leaf turn method) Muniz et al (2002) Tomato and Pepper TMB (leaf turn method) Muqit et al (2008) Tomato NDM Rafiq et al (2008) Araceae, Asteraceae, Brassicaceae, Cucurbitaceae, Chinopodiaceae, Malvaceae, Meliaceae, Papilionaceae and Solanaceae NDM Leite et al (2005) Okra TMB (leaf turn method) Naranjo et al (2003) Cotton NDM *TMB-Top, middle and bottom, **NDM-No defined method.…”
Section: Referencementioning
confidence: 99%
“…However, the S-biotype has only ever been recorded within a localised area near Malaga and only on Ipomoea indica (Banks et al, 1999). Muñiz (2000) and Nombela et al (2001) have reported differences between the host responses to B-and Q-biotypes of B. tabaci in common weeds (Datura stramonium L., Solanum nigrum, L., Brassica kaber (DC), Capsella bursa-pastoris L. and Malva parviflora L.) and tomato plants. Moreover, some differences in transmission efficiencies of the B. tabaci biotypes when transmitting TYLCV/TYLCSV from tomato to tomato have been already reported (Sánchez-Campos et al, 1999), but few experimental studies had been undertaken to date on the transmission of TYLCSV-ES (Sánchez-Campos et al, 2000).…”
Section: Resumen Nota Corta Efecto Del Biotipo De Bemisia Tabaci En mentioning
confidence: 99%
“…Five female adults of B. tabaci (B-biotype) were removed from a colony reared on tomato plants cv. Marmande, and placed into each of 10 clip-cages per assay (one cage per plant) attached to the under surface of one leaf (Nombela et al, 2001). Whiteflies were removed after 3 days, and eggs and dead individuals counted.…”
Section: Introductionmentioning
confidence: 99%